As rochas vulcânicas da Ilha São Jorge, Açores (Portugal) : petrografia e geoquímica - Mecenas, Karoline Ferreira da Silva (Pós-Graduação em Geociências e Análise de Bacias, 2019)
São Jorge Island is part of Central Group from Azores Archipelago (Portugal), which is located near the triple junction among North American, Euro-Asian and African lithospheric plates, in the North Atlantic region. The volcanism in that island is fissural type, with the preferential orientation WNW-ESE, which reveals the importance of the tectonic control during the volcanic activity. The studied magmatism is influenced by the interaction between the Hotspot of the Azores and the Meso-Atlantic Ridge. The island volcanostratigraphy is composed of three volcanic complexes named Topo (East of the island), Rosais (West of the island) and Manadas (center of the island). According to Ribeiro (2011), the oldest geochronological age reported for São Jorge Island is 1.3 ± 0.0035 Ma (40Ar / 39Ar). Based on petrographic data, the rocks of the island show medium to fine granulometry, porphyritic, microporphyritic, glomeroporphyritic, intergranular, pilotaxytic, trachytic and intersertal textures. According to geochemical data, rocks are classified as basanites (4.9-12.2% olivine, 4.6-23.2% augite, 5.4-8.3% plagioclase, 0-0.3% opaque minerals and 59.2-81.9% matrix), alkaline basalts (0.6-3.3% olivine, 0-3.5% augite, 6.3-17.5% plagioclase, 0-1, 2% kaersutite, 0-1.8% opaque minerals and 79.2-88.2% matrix) and hawaiites (0-5.6% olivine, 0-3.2% augite, 0- 22.2% plagioclase, 0-1.1% kaersutite, 0-1.6% opaque minerals and 69-99.7% matrix). The matrix presents mineralogical composition like phenocrysts composition (olivine, augite, plagioclase, kaersutite and opaque minerals), as well as volcanic glass and rounded-elongated vesicles. Reabsorption textures, sheathing, reaction edges and zonation are common features in the phenocrysts of the studied rocks. These features indicate that the magma underwent rapid decompression, with sudden variation of temperature and pressure. The trace element patterns show enrichment in LILE and HFSE relative to the ETRP. The ETR patterns present ETRL enrichment compared to ETRP, with Eu negative anomaly. These similar patterns, with subparallel trends suggest that the rocks were generated by low partial melting rates. The rocks show alkaline sodium affinity and were originated from an enriched mantle magma. The chemical data are compatible with data from magmas generated in an environment of oceanic intraplate type (OIB). A Ilha São Jorge faz parte do Grupo Central do Arquipélago dos Açores (Portugal), que está situado próximo à junção tríplice, entre as placas litosféricas Norte-Americana, Euro-Asiática e Africana, na região do Atlântico Norte. O vulcanismo nesta ilha é do tipo fissural, com a orientação preferencial WNW-ESE, o que revela a importância do controle tectônico durante a atividade vulcânica. O vulcanismo estudado é influenciado pela interação entre o Hotspot dos Açores e a Cordilheira Meso-Atlântica. A vulcanoestratigrafia da ilha é composta por três complexos vulcânicos denominados Topo (leste da ilha), Rosais (oeste da ilha) e Manadas (centro da ilha). Segundo Ribeiro (2011), a idade geocronológica mais antiga relatada para a Ilha São Jorge é 1,3 ± 0,0035 Ma (40Ar/39Ar). Com base em dados petrográficos, as rochas da ilha apresentam granulometria média a fina, texturas porfirítica, microporfirítica, glomeroporfirítica, intergranular, pilotaxítica, traquítica e intersertal. De acordo com dados geoquímicos, as rochas forma classificadas como basanitos (4,9-12,2% de olivina, 4,6-23,2% de augita, 5,4-8,3% de plagioclásio, 0-0,3% de minerais opacos e 59,2-81,9% de matriz), basaltos alcalinos (0,6-3,3% de olivina, 0-3,5% de augita, 6,3-17,5% de plagioclásio, 0-1,2% de kaersutita, 0-1,8% de minerais opacos e 79,2-88,2% de matriz) e hawaítos (0-5,6% de olivina, 0-3,2% de augita, 0-22,2% de plagioclásio, 0-1,1% de kaersutita, 0-1,6% de minerais opacos e 69-99,7% de matriz). A matriz apresenta composição mineralógica semelhante à composição dos fenocristais (olivina, augita, plagioclásio, kaersutita e minerais opacos), além de vidro vulcânico e vesículas com formas arredondadas e alongadas. Texturas de reabsorção, embainhamento, bordas de reação e zonação são feições comuns nos fenocristais das rochas estudadas e indicam que o magma sofreu descompressão rápida, com variação brusca de temperatura e pressão. Os padrões de elementos-traço mostram enriquecimento em LILE e HFSE em relação aos ETRP. Os padrões de ETR apresentam enriquecimento em ETRL em comparação aos ETRP, com anomalia negativa de Eu. Os padrões são similares, com trends subparalelos, sugerem que as rochas foram geradas por baixas taxas de fusão parcial. As rochas apresentam afinidade alcalina sódica, sendo originadas a partir de um magma mantélico enriquecido. Os dados químicos são compatíveis com dados de magmas gerados em ambiente do tipo intraplaca oceânico (OIB). São Cristóvão, SE